PEMBUATAN APLIKASI PORN BLOCKER PADA INTERNET MENGGUNAKAN BAHASA PEMOGRAMAN VISUAL BASIC 6.0 - Bendrianti, Rita Prima; Prahasti, Prahasti; Meifialdy, Thomas (Jurnal Media Infotama, 2013)
This study was conducted to make Porn Blocker Application using the Visual Basic programming language, which then will be implemented or connect using Mozilla Firefox. Data collected by conducting library research and laboratory studies, which make comparisons with similar applications with technical safety or other sites. Furthermore, the data is analyzed and designed starting from the HIPO menu structure and then directly to the menu display for blocking websites. The results of this study are Porn Blocker application can only be run in Mozilla Firefox program, because the program in addition to Mozilla Firefox already has its own application blocking. Researchers also limit the issues on this application is based on the one computer unit and can not be used for networking.